Internacionalização da pós-graduação em Ciência da Informação no Brasil: análise de redes de colaboração científica - Telmo, Flávia de Araújo (2024)
In the academic context, internationalization is an indispensable process for achieving learning excellence and allows for new approaches and theories in the process of knowledge construction. Analyzes the social network of international scientific collaboration of the Graduate Program in Information Science of the Universidade Estadual Paulista Júlio de Mesquita Filho (PPGCI/UNESP). Methodologically, it is based on documentary and field research procedures, with a quantitative-qualitative approach and application of the methodology of social network analysis. For theoretical foundation, a systematic review is carried out in national and international databases. A structure is elaborated to diagnose internationalization, based on the collaborations at the individual level, which are dimensions, components and indicators of internationalization, applied to observe the academic interactions of professors and students of PPGCI/UNESP. For data organization and construction of matrices, the Excel software, and Gephi software is used for graph representation and collaboration analysis. The results show the systematization of the international social network of PPGCI/UNESP, with emphasis on scientific production partnerships with researchers from institutions in Spain and Portugal. The mapping demonstrates the importance of the presence of a professor in the Program with a link to an international educational institution, in order to promote partnerships between international researchers, which can increase the quality of the Program and scientific production; the search for knowledge of researchers who dialogue with pioneering approaches in foreign countries; the expansion of the knowledge of the Program's researchers with research, resulting from training, partnerships and mobility, and proves the importance of investments in internationalization actions for scientific and social advancement. Finally, it proposes strategies to expand international collaboration and bring together actors with an internationalization profile for PPG. The study has an impact on the international dimension, because with the identification of international institutions and researchers, it will be possible to outline new actions for international partnerships and strengthen existing links. The study has an impact at the national and local levels, as the data strategically contribute to the visualization of the international social network of the PPGCI/UNESP, serving as a basis for achieving or maintaining better concepts in the quadrennial evaluation of the Coordination for the Improvement of Higher Education Personnel. It is concluded that there is difficulty on the part of the programs and institutions in registering the internationalization actions, since there is no single standard, and the structure presented in the study can be a model to continuously monitor the actions resulting from the activities (individual partnerships, research groups, participation in events, mobilities, publications) linked to these programs and thus be presented to the professors. students and institutions in the search for investments and tools to record the results of these interactions. Further research is proposed for the application of the framework to know the partnerships in other Information Science programs.